PENINGKATAN MINAT BACA ANAK MELALUI TAMAN LITERASI PROGRAM - Abdur Rozaq; Ahmad Nur Chozin; Khoirotun Ni’mah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2020)
By holding a Literacy Park in the village of Sumberagung, it is hoped that it will foster an interest, love and passion for reading in children. That way the children in Sumberagung village can add insight into the development of science and technology. In addition, literacy parks are a source of entertainment that provides reading materials that are recreational in nature to take advantage of free time to acquire new knowledge that is interesting or useful. The result of this service activity is an increase in children's interest in reading as seen from the more children who borrow books so that it is certain that children's reading habits increase every day, namely from one book per day to more than one book, although in practice it still has weaknesses in the form of addiction. gadgets that often occur in millennials.